2020
DOI: 10.1039/d0sc03773g
|View full text |Cite
|
Sign up to set email alerts
|

Reversible cooperative dihydrogen binding and transfer with a bis-phosphenium complex of chromium

Abstract: The reversible reaction of H2 with a bis-phosphenium complex of chromium provides a rare example of 3d transition metal/phosphenium cooperativity. Photolysis induces the activation of H2 and yields a spectroscopically...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Numerous examples of pincer ligands engaging in novel catalytic and stoichiometric MLC-related reactions have been and continue to be reported. Yet, despite the large number of pincer ligands for which MLC is based on a coordinating N atom, there are very few examples involving the next congener, phosphorus. In particular, in spite of the great value that has been proven for addition of H 2 across M–N bonds, there are relatively few examples of H 2 addition across a phosphorus metal bond and even fewer examples of the reverse elimination of H 2 . , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous examples of pincer ligands engaging in novel catalytic and stoichiometric MLC-related reactions have been and continue to be reported. Yet, despite the large number of pincer ligands for which MLC is based on a coordinating N atom, there are very few examples involving the next congener, phosphorus. In particular, in spite of the great value that has been proven for addition of H 2 across M–N bonds, there are relatively few examples of H 2 addition across a phosphorus metal bond and even fewer examples of the reverse elimination of H 2 . , …”
Section: Introductionmentioning
confidence: 99%
“…In particular, in spite of the great value that has been proven for addition of H 2 across M−N bonds, there are relatively few examples of H 2 addition across a phosphorus metal bond 21−26 and even fewer examples of the reverse elimination of H 2 . 26,27 Phosphorus has been referred to as "the carbon copy" 28 because of numerous similarities between the chemistry, including the coordination chemistry, of these elements. PCP-type pincer ligands, in which the coordinating atom of the central group is typically a formally anionic carbon, have played an important role in organometallic chemistry in recent decades.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The vast majority of these rely on second- and third-row transition metals (M = Zr, Hf, Ru, , Ir) or alkali metals . Examples with first-row metals are even more rare, and so far, these have all relied on N-heterocyclic phosphido (NHP) donor groups. The NHP ligands temper the basicity of phosphido ligands (Figure , middle), but this strategy precludes readily available diaryl- and dialkylphosphido groups in MLC with first-row metals.…”
Section: Introductionmentioning
confidence: 99%
“…Gudat and co-workers have shown that a metal phosphenium complex, ( u NHP Dipp )­Mn­(CO) 4 ( A ), is active for the catalytic dehydrogenation of ammonia borane and ( u NHP Dipp ) 2 Cr­(CO) 3 ( B ) cooperatively activates hydrogen across a Cr–P bond and is active for the photocatalytic hydrogenation of styrene (Scheme ). , Herein, we explore the catalytic activity of (PPP)Co complexes toward alkene hydroboration, hypothesizing that metal–phosphorus cooperativity may be a viable reaction pathway.…”
Section: Introductionmentioning
confidence: 99%